Halal Kitchen Hoteland Its Opportunities in the Muslim Tourist Market - หะยีหมัด หมะหมูด; Hasama, Aris; Noipom, Tawat Noipom; BostanAli, Wanamina (Business Administration and Management Journal Review, 2020)
Muslim tourist is considered a large and growing tourist market. Providing Halal hotel services to accommodate Muslim tourist is an indispensable element of business in the tourism industry.This research aims to examine the understanding about Halal kitchen hotel, its service marketing mix, obstacles and trends. In-depth interview was used to collect the information from 15 stakeholders in 8 types of businesses in Halal tourism industry. The results indicated that, in Thailand context, there is no full-fledge Halal hotel which conform to Islamic law. However, there are 2 hotels with halal kitchen or Muslim friendly hotel. Moreover, service marketing mix that follow the Islamic principles will make Muslim tourists satisfied. For the Muslim tourism market, there is a growing trend from ASEAN countries and China. The main obstacles faced by Halal kitchen hotels were the lack of Muslim staffs and Muslim professional managers. Finally, Halal kitchen hotel with good management will gain more competitive advantage in the growing Muslim tourist market.